Max Einstein Saves the Future - Patterson, James 1947-; Grabenstein, Chris; Johnson, Beverly (New York : JIMMY Patterson Books/Little, Brown and Company, 2020)
"Max is back with a thrilling new adventure that involves time travel, creepy bad guys, killer drones, and a shocking mystery about her past that she will stop at nothing to solve!"--Provided by publisher.
Keywords: Time travel -- Juvenile fiction; Problem solving in children -- Juvenile fiction; Creative ability -- Juvenile fiction; Genius -- Juvenile fiction; Time travel -- Fiction; Problem solving -- Fiction; Creative ability -- Fiction; Genius -- Fiction